Heat transfer and hydraulic losses in the gap between rotating cylinders - Мочалин, Евгений Валентинович; Юрьев, Сергей Александрович (Technology audit and production reserves, 2013)
Despite the large number of works devoted to the study of flow between coaxial rotating cylinders, little attention was given to the issues related to the complex influence of complementary factors, such as surface roughness and surface relief, the presence of the forced flow of fluid through the annular gap, on the heat transfer and flow structure. This is due to a major complication formulation of the problem when these additional factors are considered. At the same time, these factors must be considered in order to cover the existing practical applications. In this paper we examine the effect of roughness and surface relief, the forced flow of fluid through the annular gap on heat transfer between the cylinders and flow, as well as on hydraulic losses. A comparison of exiting data about impact of various factors on heat transfer and hydraulic losses is carried out on the common methodological basis. The examination is based on the known results about the impact of forced axial flow and longitudinal grooves on the cylinders surface and includes the recent data of numerical simulation of Taylor-Couette problem with radial through-flow. The results show that the radial flow through the surface of rotating cylinder provides a substantially larger increase in the heat transfer coefficient in comparison with other examined methods. The data obtained justify the new way of improvement of the technical devices that implement convective heat transfer near the surface of a rotating cylinder